Five-Year Symptom Trajectories in Nondialysis-Dependent CKD Patients. Issue 11 (November 2022) - Faye, Moustapha; Legrand, Karine; Le Gall, Lisa; Leffondre, Karen; Omorou, Abdou Y.; Alencar de Pinho, Natalia; Combe, Christian; Fouque, Denis; Jacquelinet, Christian; Laville, Maurice; Liabeuf, Sophie; Massy, Ziad A.; et al.
Visual Abstract: Abstract : Background and objectives: Late stages of CKD are characterized by significant symptom burden. This study aimed to identify subgroups within the 5-year trajectories of symptom evolution in patients with CKD and to describe associated patient characteristics and outcomes. Design, setting, participants, & measurements: Among 2787 participants (66% men) with eGFR <60 ml/min per 1.73 m 2 enrolled in the CKD–Renal Epidemiology and Information Network (CKD-REIN) cohort study from July 2013 to May 2016, we assessed symptoms annually using the Kidney Disease Quality of Life-36 (KDQOL-36) questionnaire until December 2020. A total of 9121 measures were reported over follow-up; all participants had symptoms scored for at least one time point. We used a joint latent class-mixed model to distinguish profiles of symptom trajectories. Results: Patient mean age (±SD) at baseline was 67±13 years, and mean eGFR was 33±13 ml/min per 1.73 m 2 . The prevalence of each symptom ranged from 24% (chest pain) to 83% (fatigue), and 98% of participants reported at least one symptom. After a median (interquartile range) follow-up of 5.3 (3.4–6.0) years, 690 participants initiated KRT, and 490 died before KRT. We identified two profiles of symptom trajectories: a "worse symptom score and worsening trajectory" in 31% of participants, characterized by a low initial symptom score that worsened more than ten points over time, and a "better symptom score and stable trajectory" in 69% of participants, characterized by a high initial score that remained stable. Participants in the worse symptom score and worsening trajectory group had more risk factors for CKD progression at baseline, worse quality of life, and a higher risk of KRT and death before KRT than other participants. Conclusions: This study highlights a significant worsening of symptoms in about one third of the participants, whereas the majority reported low symptom severity throughout the study.